Primitive Malignant Melanoma of Gall Bladder - Castiglioni, Juan C; Piacenza, Guillermo; Viñuela, Enrique; Turturiello, Horacio; Falconi, Luis (Cirugía del Uruguay, 1980)
Report on a rare case of primitive malignant melanoma in gall bladder. Clinically it appeared as obstructive jaundice, resulting from biliary obstruction due to residues detached from tumor which occluded common duct lumen.